Restrictions on Medical Practice from the Perspective of Dignified Justice - Sutardi, Gregorius Batara Putra Setia (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2025)
Justice always exists alongside Law. Where the law will overcome injustice in terms of medical practice, it can be seen in the formulation of the 1945 Constitution of the Republic of Indonesia, Article 28 H section 1 every person has the right to live in physical and spiritual prosperity, to live, and have a good and healthy living environment and the right to health services. Injustice in the limitation of medical practice can be described in the existence of a law that is just and dignified. The description of dignified justice in the limitation of medical practice is contained in Law No. 36 of 2014 concerning Health Workers.